Penerapan Standar Akuntansi Mikro dalam Usaha Kuliner: Studi Kasus UMKM Sempolan Kabupaten Tegal - Deni Setiawan; Liris Kristina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, particularly in the culinary sector. However, most MSMEs still face challenges in financial management due to limited understanding of accounting. This study aims to analyze the application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) to the Sempolan culinary business and its impact on the quality of business financial management. The research method used is a qualitative approach with a case study. Data were obtained through interviews, observations, and documentation. The results show that the application of SAK EMKM can improve the regularity of financial records, transparency of reports, and assist business actors in decision-making. Despite obstacles such as limited accounting literacy and human resources, the application of micro accounting standards still provides significant benefits for the sustainability of culinary MSMEs.